2009
DOI: 10.1007/s00268-009-0178-0
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk in Patients with Nonfunctional Adrenal Incidentaloma: Myth or Reality?

Abstract: Patients with NFA have increased prevalence of metabolic syndrome and impaired endothelial function compared with 1:1 cardiometabolic risk factor-matched controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 21 publications
4
11
0
Order By: Relevance
“…In a previous report, even patients with nonfunctioning AIs (defined as cortisol level <1.8 mg/dL after LDDST) also had less FMD compared with age-matched, sex-matched, BMI-matched subjects and cardiometabolic controls. 19 A very recent study by Debono and colleagues 20 also confirmed this association. In a retrospective study of 206 patients, all with adrenal adenomas, patients were categorized as having cortisol concentrations greater than 1.8 mg/dL after 1-mg LDDST or having cortisol concentrations less than 1.8 mg/dL after 1-mg LDDST.…”
Section: Cardiovascular Diseasesupporting
confidence: 57%
“…In a previous report, even patients with nonfunctioning AIs (defined as cortisol level <1.8 mg/dL after LDDST) also had less FMD compared with age-matched, sex-matched, BMI-matched subjects and cardiometabolic controls. 19 A very recent study by Debono and colleagues 20 also confirmed this association. In a retrospective study of 206 patients, all with adrenal adenomas, patients were categorized as having cortisol concentrations greater than 1.8 mg/dL after 1-mg LDDST or having cortisol concentrations less than 1.8 mg/dL after 1-mg LDDST.…”
Section: Cardiovascular Diseasesupporting
confidence: 57%
“…In 2009, Erbil et al [9] compared a group of patients with confirmed non-functioning adenomas against age and body-mass index matched controls. They reported decreased flow mediated dilatation, along with an increased prevalence of the metabolic syndrome, in the adenoma group.…”
Section: Discussionmentioning
confidence: 99%
“…However, long-term data on the natural evolution and potential changes in size and pattern of secretion of these tumours is still scarce. Increasing evidence suggests that even the apparently non-functioning adrenal adenomas may be associated with higher prevalence of hypertension and a variety of metabolic abnormalities such as obesity, diabetes mellitus type 2, impairments of glucose metabolism and dyslipidaemia compared to the general population [11][12][13][14][15][16][17][18][19]. These derangements are usually explained by subtle autonomous hormonal secretion, mostly of cortisol, that is insufficient to cause the typical clinical manifestations of overt Cushing's syndrome.…”
Section: Introductionmentioning
confidence: 99%